Classical and Bayesian Inference of Conditional Stress-Strength Model under Kumaraswamy Distribution. (31st July 2021) - Riad, Fathy H.; Saber, Mohammad Mehdi; Taghipour, Mehrdad; El-Raouf, M. M. Abd
Abstract : Stress-strength models have been frequently studied in recent years. An applicable extension of these models is conditional stress-strength models. The maximum likelihood estimator of conditional stress-strength models, asymptotic distribution of this estimator, and its confidence intervals are obtained for Kumaraswamy distribution. In addition, Bayesian estimation and bootstrap method are applied to the model.